[PP.03.21] TELOMERE LENGTH AND ATHEROSCLEROTIC CARDIOVASCULAR DISEASE: THE BLOOD-AND-MUSCLE MODEL. (September 2017) - Benetos, A.; Verhulst, S.; Gautier, S.; Labat, C.; Toupance, S.; Kimura, M.; Rossi, P.M.; Settembre, N.; Hubert, J.; Frimat, L.; Bertrand, B.; Boufi, M.; et al.
Abstract : Objective: Short telomere length (TL) in leukocytes is associated with atherosclerotic cardiovascular disease (ACVD). It is unknown whether this relationship is due to a shorter leukocyte TL (LTL) at birth or, alternatively, to a faster LTL attrition thereafter, before or during ACVD manifestation. To assess the temporal relation of LTL with ACVD, we draw on the following findings: wide LTL variation exists across individuals, but at birth TLs are similar across the individual's somatic tissues. After birth, TL attrition varies in proportion to the replicative activities of tissues. Consequently, skeletal muscle (M), a minimally proliferative tissue, displays a longer TL than LTL, which represents the highly proliferative hematopoietic system. Accordingly, the difference between LTL and MTL and the ratio of (LTL-MTL)/MTL provides additional information on LTL attrition since early life. Design and method: We studied 271 individuals (82 women/189 men) aged 63 ± 14 years (mean ± SD), undergoing surgery. Their TL in leukocytes and in muscle biopsies (obtained during surgery) was measured by Southern blots. We tested the following variables for association with ACVD: LTL, MTL adjusted for muscle biopsy site (MTLA), LTL-MTLA and (LTL-MTLA)/ MTLA. Results: In all subjects, MTLA was longer than LTL and LTL-MTLA difference became wider with age similarly in ACVD patients (15.9 ± 0.5 bp/year; mean ± SE) and controls (14.4 ± 0.3 bp/year). Age- and sex-adjusted LTL (P = 0.005), but not MTLA (P = 0.68), was shorter in patients with ACVD than controls. LTL-MTLA (−272 ± 73 bp) and (LTL-MTLA)/MTLA (−3.2 ± 0.8%) were wider in ACVD than in controls (P = 0.0003 and 0.0001, respectively). Both composite variables that combined LTL and MTL yielded better fitting models than either LTL or MTLA by themselves, and (LTL-MTLA)/MTLA explained ACVD slightly better than LTL-MTLA. Conclusions: This first study applying the "blood-and-muscle" TL model in patients with ACVD shows more pronounced TL attrition in ACVD patients than controls. The difference in attrition rates was not modified by age during adulthood indicating that accelerated attrition in early life is likely to be a major explanation of the shorter LTL in ACVD patients.